2000
DOI: 10.4049/jimmunol.164.9.4955
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Colony-Stimulating Factor Antagonists Inhibit Replication of HIV-1 in Human Macrophages

Abstract: Macrophages infected with HIV-1 produce high levels of M-CSF and macrophage-inflammatory protein-1α (MIP-1α). M-CSF facilitates the growth and differentiation of macrophages, while the chemotactic properties of MIP-1α attract both T lymphocytes and macrophages to the site of HIV infection. Studies described in this work indicate M-CSF may function in an autocrine/paracrine manner to sustain HIV replication, and data suggest possible therapeutic strategies for decreasing viral load following HIV infection. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…Thus, it appears that IL-32 functions as a negative regulator of HIV-1 in a feedback loop. In this study, however, we demonstrated that M-CSF, which is present at relatively high concentrations in human serum (37), is essential for the development of most tissue macrophages (11)(12)(13), and stimulates the HIV-1 replication (17)(18)(19)(20)(21), markedly counteracts the anti-HIV-1 activity of IL-32g (Figs. 3 and 4).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Thus, it appears that IL-32 functions as a negative regulator of HIV-1 in a feedback loop. In this study, however, we demonstrated that M-CSF, which is present at relatively high concentrations in human serum (37), is essential for the development of most tissue macrophages (11)(12)(13), and stimulates the HIV-1 replication (17)(18)(19)(20)(21), markedly counteracts the anti-HIV-1 activity of IL-32g (Figs. 3 and 4).…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, M-CSF has been demonstrated to stimulate HIV-1 replication (17)(18)(19)(20)(21). Thus, we next investigated how cotreatment with M-CSF and IL-32g affects HIV-1 replication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Unlike monocyte-derived macrophages (MDMs), undifferentiated monocytes are not readily infected by HIV-1 in cell culture. 16,17 A productive viral infection may only occur after monocytes are differentiated after serum or cytokine stimulation, 18 a process that leads to the up-regulation of different cell-surface markers and receptors, including ␣V integrins 19,20 and, more specifically, an increase in the vitronectin ␣V␤3 receptor during the first 3 to 6 hours after infection. 14 We and others have shown the antiviral effect of specific anti-␣V antibodies in MDMs.…”
Section: Introductionmentioning
confidence: 99%